Relationship of Arterial Stiffness Index and Pulse Pressure With Cardiovascular Disease and Mortality. Issue 2 (22nd January 2018) - Said, M. Abdullah; Eppinga, Ruben N.; Lipsic, Erik; Verweij, Niek; van der Harst, Pim
Abstract : Background: Vascular aging results in stiffer arteries and may have a role in the development of cardiovascular disease (CVD). Arterial stiffness index (ASI), measured by finger photoplethysmography, and pulse pressure (PP) are 2 independent vascular aging indices. We investigated whether ASI or PP predict new‐onset CVD and mortality in a large community‐based population. Methods and Results: We studied 169 613 UK Biobank participants (mean age 56.8 years; 45.8% males) who underwent ASI measurement and blood pressure measurement for PP calculation. Mean±SD ASI was 9.30±3.1 m/s and mean±SD PP was 50.98±13.2 mm Hg. During a median disease follow‐up of 2.8 years (interquartile range 1.4–4.0), 18 190 participants developed CVD, of which 1587 myocardial infarction (MI), 4326 coronary heart disease, 1192 heart failure, and 1319 stroke. During a median mortality follow‐up of 6.1 years (interquartile range 5.8–6.3), 3678 participants died, of which 1180 of CVD. Higher ASI was associated with increased risk of overall CVD (unadjusted hazard ratio 1.27; 95% confidence interval [CI], 1.25–1.28), myocardial infarction (1.38; 95% CI, 1.32–1.44), coronary heart disease (1.31; 95% CI, 1.27–1.34), and heart failure (1.31; 95% CI 1.24–1.37). ASI also predicted mortality (all‐cause, CVD, other). Higher PP was associated with overall CVD (1.57; 95% CI, 1.55–1.59), myocardial infarction (1.48; 95% CI, 1.42–1.54), coronary heart disease (1.47; 95% CI, 1.43–1.50), heart failure (1.47; 95% CI, 1.40–1.55), and CVD mortality (1.47; 95% CI, 1.40–1.55). PP improved risk reclassification of CVD in a non–laboratory‐based Framingham Risk Score by 5.4%, ASI by 2.3%. Conclusions: ASI and PP are independent predictors of CVD and mortality outcomes. Although both improved risk prediction for new‐onset disease, PP appears to have a larger clinical value than ASI.